2022
DOI: 10.15421/012238
|View full text |Cite
|
Sign up to set email alerts
|

The degradation of forest areas in Morocco: Case of Benslimane province

Abstract: This article aims to shed light on the process of known degradation of the forest area of Benslimane province during the period 1990–2020 and to specify the most important human causes which contributed to it (quarries, extension of the built-up area, the impact of agricultural activities, grazing and collection of firewood), by using remote sensing techniques (spatial images for the years 1990–2000–2010–2020) to produce Land Cover maps. The following satellite images were used, Landsat 5 TM, Landsat 7 ETM+ an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…The degradation of important marine areas in Morocco is primarily due to increased economic and population activity in coastal areas, water pollution, and overfishing [24,37]. Likewise, the forest environment is threatened by unsustainable extraction of nontimber products, overgrazing, and clearing for agriculture and urbanization [38]. The area of urbanized land in Morocco is increasing annually, with more than 60% of the population living in urban areas [39].…”
Section: Marine and Forest Environment Ecosystems In Moroccomentioning
confidence: 99%
“…The degradation of important marine areas in Morocco is primarily due to increased economic and population activity in coastal areas, water pollution, and overfishing [24,37]. Likewise, the forest environment is threatened by unsustainable extraction of nontimber products, overgrazing, and clearing for agriculture and urbanization [38]. The area of urbanized land in Morocco is increasing annually, with more than 60% of the population living in urban areas [39].…”
Section: Marine and Forest Environment Ecosystems In Moroccomentioning
confidence: 99%
“…Forests and woodland ecosystems in Morocco have a vital role in preserving biodiversity and supplying ecological and economic benefits (Serbouti et al, 2023), such as providing habitat for millions plants and animals (Eyvindson et al, 2018), and combat against the desertification (Benzyane, 2007). Moreover, the forestry industry in Morocco has played a significant role in the country's economy, making the largest economic contribution (African Developemnt Bank, 2000), as the quantity of wood extracted from the Moroccan forest reaches 10 million m 3 /year (Benzyane, 2007;Hammouyat et al, 2022) . In addition, Forest areas in Morocco cover 9 million hectares, which accounts for 12% of the national territory (Laaribya et al, 2017), This wealth is due to the uniqueness from a geographic, climatic, and ecological perspective (Berrahmouni & Christophe, 2013), the most representative forests in Morocco are Tetraclinis articulata forest with an area of 450,000 ha, Argania spinosa 450,000 ha, Quercus rotundifolia 400,000 ha and Quercus suber 400,000 ha (des Eaux & du Maroc, 1927).…”
Section: Introductionmentioning
confidence: 99%
“…Landsat is widely used (Ait El Haj et al, 2023;Cai et al, 2020;Dhaloiya et al, 2023;Milanović et al, 2019) by application of NDVI index (Ozyavuz, et al, 2015;Sonali et al, 2021) and supervised classification (Bispo et al, 2013;Salata, 2021). A study in Benslimane, nearby area, is carried out by Hammouyat et al, using the same process, revealed that the forest is declined by 11.4 % losing nearly 200 ha/year (Hammouyat et al, 2022), andHoussni et al (2018) showed that high formations, low formations, and matorrals have regressed by 62%, 70%, and 49% respectively in the Western Rif region of Morocco (Houssni et al, 2018).…”
Section: Introductionmentioning
confidence: 99%